Adalimumab therapy for refractory uveitis: results of a multicentre, open-label, prospective trial. Issue 4 (2nd February 2013) - Suhler, Eric B; Lowder, Careen Y; Goldstein, Debra A; Giles, Tracy; Lauer, Andreas K; Kurz, Paul A; Pasadhika, Sirichai; Lee, Shelly T; de Saint Sardos, Alexandre; Butler, Nicholas J; Tessler, Howard H; Smith, Justine R; et al.
Abstract : Objective: Tumour necrosis factor (TNF) blockers have been demonstrated to be effective in the treatment of systemic and ocular inflammatory diseases. We conducted a prospective, multicentre, open-label Phase II clinical trial to assess the effectiveness and safety of adalimumab, a fully human anti-TNF monoclonal antibody, in treating refractory uveitis. Methods: Subjects with non-infectious uveitis refractory to corticosteroids and at least one other immunosuppressive medication were enrolled. Treatment outcome was ascertained by a composite endpoint comprised of visual acuity, intraocular inflammation, ability to taper immunosuppressives, and posterior segment imaging. Clinical response was defined by improvement in at least one parameter, worsening in none, and well controlled intraocular inflammation. Week 10 responders were permitted to continue receiving adalimumab for the study duration of 50 weeks. Results: Twenty-one of 31 patients (68%) were characterised as clinical responders at 10 weeks, of whom 12 patients (39%) exhibited durable response after 50 weeks. The most common reason for study termination was primary or secondary inefficacy. No patients experienced treatment-limiting toxicity clearly related to study therapy. Conclusions: Adalimumab was safe and effective in 68% of refractory uveitis patients 10 weeks after study enrolment, and maintained in 39% after 1 year. Ongoing study is required to determine the place of adalimumab and other TNF blockers in the treatment of uveitis.